1998
DOI: 10.1016/s0014-5793(98)00386-x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in chain length distribution of inulin fromCynara scolymusandHelianthus tuberosusare reflected in a transient plant expression system using the respective 1‐FFT cDNAs

Abstract: A newly isolated cDNA clone, Cy3, encoding the fructan fructan 1-fructosyltransferase (1-FFT) from artichoke was expressed using tobacco protoplasts as expression system. Analysis of the inulin molecules synthesized upon incubation of protoplast extracts with a mixture of oligofructans (DP3^5) shows the production of inulins with a degree of polymerization (DP) of up to 23, whereas parallel experiments performed using a 1-FFT cDNA from Jerusalem artichoke led to the production of fructans with a DP of up to on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 25 publications
0
55
0
1
Order By: Relevance
“…Alternatively, distinct enzymatic properties should be taken into account. We have reported that 1-FFT of globe artichoke shows a preference for higher DP substrates as acceptor of transferred fructosyl residues than does the enzyme from Jerusalem artichoke (18). Under conditions where high invertase activity prevents accumulation of lower molecular weight inulin molecules, which are the main products formed by the H. tuberosus 1-FFT, the C. scolymus enzyme would be more efficient in synthesizing higher-order inulin molecules, which are less accessible to invertases (31).…”
Section: Accumulation Of High Molecular Weight Inulin In Plants Exprementioning
confidence: 93%
See 2 more Smart Citations
“…Alternatively, distinct enzymatic properties should be taken into account. We have reported that 1-FFT of globe artichoke shows a preference for higher DP substrates as acceptor of transferred fructosyl residues than does the enzyme from Jerusalem artichoke (18). Under conditions where high invertase activity prevents accumulation of lower molecular weight inulin molecules, which are the main products formed by the H. tuberosus 1-FFT, the C. scolymus enzyme would be more efficient in synthesizing higher-order inulin molecules, which are less accessible to invertases (31).…”
Section: Accumulation Of High Molecular Weight Inulin In Plants Exprementioning
confidence: 93%
“…The 1-SST (17) and 1-FFT cDNAs (18) were subcloned separately into the binary vector pBinAR, a derivative of the pBin19 vector (19). The cDNAs contain endogenous signal sequences for a predicted vacuolar localization of the encoded enzymes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11,16) Sprenger et al 16)ˆr st reported the cloning of a plant gene of the fructan biosynthesis enzyme 6-SFT from Hordeum vulgare. Since then, several genes encoding enzymes in fructan biosynthesis have been cloned from various plants: 1-SST from C. intybus; 19) 1-SST and 1-FFT from Cynara scolymus 20,21) and from H. tuberosus; 22) 1-SST and 6G-FFT from Allium cepa; 18,23) and 1-SST from Festuca arundinacea; 24) and 6-SFT from Agropyron cristatum. 12) We have identiˆed cDNAs for 1-SST and 6-SFT from wheat, and this is theˆrst report of cloning 1-SST and 6-SFT from the same plant.…”
mentioning
confidence: 99%
“…Fungal as well as plant genes have successfully been expressed in yeast systems (20,31), and several plant fructosyltransferases have been expressed in transformed plants or protoplasts (7,16,38,39,47). Because plant fructosyltransferases are vacuolar enzymes (9), it can be assumed that posttranslational modification is necessary for enzymatic function and thus prevents functional expression in bacterial systems.…”
Section: Discussionmentioning
confidence: 99%